Identification of voltage-gated calcium currents in Helix (Cornu) serotonergic neurons, subcellular localization, and role in calcium dynamics and cellular firing of CaV2.1 and CaV2.2 subtypes - Ríos-Reyes, María Laura; Calvo-Corea, Silvia; Brenes, Oscar (Frontiers in Biophysics, 2025)
Calcium not only contributes to changes in membrane potential but also acts as a central regulator of multiple cellular processes. Invertebrates have had a critical role throughout history as biological models for studying the nervous system at the cellular level due to the relative simplicity of their neural circuits and their high resistance to experimental manipulation. Among them, land snails of the genus Helix present the previously described characteristics while also being easy to maintain in the laboratory, and their neurons in culture reproduce in vitro their in vivo characteristics. However, the electrophysiological properties of their neurons remain incompletely characterized, and thoroughly understanding the biological model is essential to fully exploit its capabilities. To better characterize the ionic properties and distribution of the voltage-gated calcium channels (CaVs) in the serotonergic C1 neuron of Helix aspersa, we employed patch clamp recordings, calcium imaging and immunocytochemistry. Our results indicate that the C1 neuron exhibits exclusively high-voltage activated calcium currents and, according to the pharmacological dissection, these are mediated by CaV2.1 and CaV2.2-like channels. The CaV2.2-like channels were primarily localized in neurites, whereas functional varicosities, those expressing exocytic machinery, predominantly contain CaV2.1-like channels.